STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PENANANAMAN NILAI-NILAI AKHLAK SISWA SMA NEGERI I SEKAMPUNG LAMPUNG TIMUR - Ibnu Mas’ud; Arsad Ali Fahmi; Ahmad Abroza (IAIN Padangsidimpuan, 2018)
This study aims to determine the strategy applied by Religious teachers to the students, to determine the effectiveness of the strategies used in the development of character and to explore the constraints faced by the Islamic religious teachers in the implementation of the strategy in Senior High School state (SMAN) I of Sekampung. This study included a qualitative descriptive study. Research data collection is done by observation and interview techniques, while the authors analysis using qualitative descriptive analysis techniques, namely in the form of data written or verbal behavior of people and observed that in this case the author seeks to undertake research which illustrates the overall nature of the real situation. Results of research showed that the strategies that teachers of religion in instilling religious values to students in the form of all efforts related to the development of character. It was done inside and outside the classroom with various kinds of strategies and methods that are considered effective for the students' moral development. Moreover, for the obstacles encountered an obstacle of internal and external factors, especially infrastructure is inadequate for optimal learning process